Pemberdayaan Ibu Rumah Tangga melalui Pengolahan Limbah Organik di Desa Pasirukem, Kabupaten Karawang - Indrajit Wicaksana; Yuridistya Primadhita; Anggraita Primatami; Idham Maulana Oktora (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aims to enhance the capacity of women in Pasirukem Village, Karawang Regency, to manage household organic waste. The main challenges faced by Pasirukem Village include the high volume of organic waste that has not been optimally managed and the limited public knowledge of household-based waste processing. The methods employed consist of counseling, hands-on training in processing organic waste into compost and liquid fertilizer, and group mentoring to support the implementation of these techniques. The results demonstrate improvements in participants’ knowledge, skills, and environmental awareness. In addition, the women have been able to produce compost and liquid fertilizer that can be utilized for household-scale agricultural activities and have the potential to increase family income. This program contributes to waste reduction, the improvement of household economic conditions, and the strengthening of women’s roles in sustainable development in Pasirukem Village